FROM PLANTATION TO CONGREGATION: GOVERNANCE AND ACCOUNTABILITY OF A MOSQUE-MANAGED PALM OIL BUSINESS AT DARUSSALAM MOSQUE, INDONESIA - Netta Agusti; Bagus Setia Wahyudi; Ashadi Cahyadi (JURNAL MANAJEMEN DAKWAH, 2025)
Mosques in Indonesia have historically relied on traditional philanthropic sources: infaq, sedekah, waqf and grants from government and private entities. Conversely, productive funding models have remained systematically underdeveloped. This study aims to analyze the dynamics and accountability of a mosque funding model based on a palm oil plantation. It further evaluates the scheme's potential as an alternative for fulfilling the mosque's religious, economic, and social functions. The study employs a qualitative approach, utilizing a single case study methodology focused on Darussalam Mosque in Mukomuko Regency, Indonesia. Data were collected through in-depth interviews, passive-participant observation, and analysis of local archival documentation. The findings indicate that the SSTBS (Sedekah Satu Tanda Buah Sawit) scheme, combined with plantation management, successfully established a sustainable funding source that supports the mosque's physical infrastructure development. However, accountability for this management remains informal, relying heavily on trust-based relationships rather than a documented administrative system. Despite this limitation, the model demonstrates significant potential for replication by other mosques, particularly those within agrarian communities, contingent upon the strengthening of institutional and financial governance. This study contributes to the discourse on productive asset-based mosque financing, a topic largely unexplored within the field of da'wah management.